Fabrication and Characterisation of Eutectic Cast Alloy from Aluminium and Copper Wastes - Nor Hasnina Asmat; Badarulzaman, Nur Azam (Research Progress in Mechanical and Manufacturing Engineering, 2025)
This project investigates the fabrication and characterisation of aluminium-copper (Al–Cu) eutectic cast alloys using recycled metal waste materials. The primary aim was to explore the viability of repurposing scrap aluminium and copper into hypoeutectic (15% Cu), eutectic (33% Cu), and hypereutectic (40% Cu) alloy compositions. The methodology involved material collection, alloy preparation, casting, and mechanical and microstructural characterisation using hardness testing, impact resistance, optical microscopy, SEM, and EDX. Despite following precise fabrication processes, results showed that the intended compositions were not fully achieved due to copper impurity, equipment limitations, and inadequate homogenisation during melting. All specimens exhibited similar aluminium-rich microstructures and low mechanical performance, with hardness values averaging around 75–95 HV and minimal presence of the θ-phase. The lack of distinction in mechanical and structural characteristics among the samples indicates a significant deviation from the target eutectic and hypereutectic structures. This highlights the importance of material purity and process control when using waste materials for advanced alloy development. Nonetheless, the study demonstrates a foundational approach to sustainable alloy production through metal recycling, with recommendations for future improvements.